(untitled) (Global Journal of Science Frontier Research, 2025)
The quality of soil preparation for greenhouses is a key factor influencing crop yields in organic farming. Several machines perform various operations for working with greenhouse soil: a soil removal machine, a loader-mixer for soil components, and a machine for laying soil components. Theoretical research has established that the greatest influence on the power of the component laying machine comes from: the speed of the conveyor chain, the angular velocity of the dosing drum, the number of conveyor scrapers, and the number of drum slats. For the power of the soil removal machine, the influencing factors are: the size of the cut soil layer, the speed of the machine itself, and the angle of the bucket surface.